The Effects of Industry Specialization on Auditors' Inherent Risk Assessments and Confidence Judgements* - TAYLOR, MARK H. (Contemporary Accounting Research, 2000)
This study experimentally examines how industry specialization affects auditors' inherent risk assessments and their confidence in those risk assessments. Two groups of participants ‐ experienced banking specialist auditors and equally experienced nonbanking auditors ‐ provided inherent risk assessments for a hypothetical banking client for two financial statement accounts. They assessed inherent risk for an industry‐specific account (loans receivable) and for a nonindustry‐specific account (property and equipment). The results indicate that nonbanking auditors assessed inherent risk significantly higher than industry specialists for all but the valuation assertion for the loans receivable account. However, the difference between the nonbanking auditors' and banking specialists' inherent risk assessments was not as great for the property and equipment account. Further, nonspecialists were less confident about the appropriateness of their inherent risk assessments compared with industry specialists. Potential implications for research and practice are discussed in light of the study's findings.